ANALISIS STRATEGI PEMASARAN (STUDI KASUS PADA AKUN INSTAGRAM @SR12BEAUTYCENTRE.ID KLINIK ELSKO DISTRIBUTOR BENGKULU) - Sari, Deka Mayang; Riswanto, Riswanto (Program Studi Ilmu Komunikasi, Universitas Muhammadiyah Bengkulu, 2024)
An online marketing communication strategy is very necessary to achieve a sales goal, especially through Instagram social media on the Instagram account @sr12beautycentre.id. This research aims to determine the online marketing communication strategy on the Instagram account @sr12beautycentre.id at the Elsko clinic, Sr12 herbal distributor, Bengkulu. In this research, a qualitative method was used with a descriptive approach using an analysis knife on the concept of marketing communication strategy theory, namely IMC (Integreatad Marketing Communication). The informant subjects in this research were the owner of the Elsko SR12 herbal clinic in Bengkulu, 4 employees, and 3 active consumers at the Elsko clinic. Data collection techniques are carried out directly in the form of observation and in-depth interviews with sources in order to obtain results that are relevant and in accordance with the research objectives, and documentation is a complement to the data collection techniques in this research. The research results show that the online marketing communication strategy carried out by the Elsko clinic is general marketing by carrying out activities such as creating advertisements or content that utilizes the features of the Instagram application, direct response strategies by providing good responses to consumers, going live on the Instagram social media platform, sales promotion, namely by providing the best offers in the form of cash back of 100 thousand for every purchase of data of 500 thousand, discounts, free treatment, and public relations which have been carried out, namely by establishing relationships between the company and consumers such as saving WA contacts or followers from media accounts Instagram social to provide information to internal or external parties by communicating online Keywords : Strategy, Online Marketing communication, informants, and Sr12 Bengkulu